Relationship between stem diameter and transpiration for Japanese cypress trees: Implications for estimating canopy transpiration - Tsuruta, Kenji; Komatsu, Hikaru; Kume, Tomonori; Otsuki, Kyoichi; Kosugi, Yoshiko; Kosugi, Ken'ichiro (Ecohydrology, 2019)
Previous studies reported relationships between stem diameter at breast height (DBH) and whole‐tree transpiration (Qt) across a variety of species and locations. It might be possible to develop a relationship between DBH and Qt with smaller variations when we focused on a single species. We attempted to develop such a relationship for Japanese cypress (Chamaecyparis obtusa), which is one of the major plantation species in Japan. We collated Qt for 51 Japanese cypress trees from nine different‐sized and different‐aged stands using the sap flux method. We found a strong linear correlation between DBH and the reference value of Qt at a vapour pressure deficit of 1 kPa (R = .883). This was a consequence of a strong correlation between DBH and sapwood area (AS_tree; R = .973) and the absence of a correlation between DBH and sap flux density (R = −.043). We confirmed that using the relationship between DBH and AS_tree, while assuming typical responses of sap flux density to meteorological factors, provides reasonable Qt estimates. This study also demonstrated how the DBH–Qt relationship can be applied to estimate changes in EC with changing forest management.